Two-photon microscopy of fungal keratitis-affected rabbit cornea ex vivo using moxifloxacin as a labeling agent. (September 2018) - Lee, Jun Ho; Le, Viet-Hoan; Lee, Seunghun; Park, Jin Hyoung; Lee, Jin Ah; Tchah, Hungwon; Kim, Sungjee; Kim, Myoung Joon; Kim, Ki Hean
Abstract: Two-photon microscopy (TPM) is a three dimensional (3D) microscopic technique based on nonlinear two-photon fluorescence, which has been tested as an alternative to reflectance confocal microscopy (RCM) for detecting fungal keratitis via optical imaging. Although TPM provided images with better contrast than RCM for fungal keratitis, its imaging speed was relatively low because of weak intrinsic signal. Moxifloxacin, a Food and Drug Administration (FDA)-approved antibiotic, was recently used as a cell-labeling agent for TPM. In this study, moxifloxacin was used to label fungal cells for TPM imaging of fungal keratitis models. Fungal cell suspensions and ex vivo fungal keratitis-affected rabbit corneas were prepared using two types of fungal pathogens, Aspergillus fumigatus and Candida albicans, and TPM imaging was performed both with and without moxifloxacin treatment. Fungal cells with enhanced fluorescence were clearly visible by TPM of moxifloxacin-treated fungal cell suspensions. TPM of moxifloxacin-treated fungal keratitis rabbit corneas revealed both the infecting fungal cells and corneal cells similar to those observed in TPM without moxifloxacin treatment, albeit with approximately 10-times enhanced fluorescence. Fungal cells were distinguished from corneal cells on the basis of their distinct morphologies. Thus, TPM with moxifloxacin labeling might be useful for the detection of fungal keratitis at the improved imaging speed. Highlights: TPM with moxifloxacin labeling was used for detecting fungal pathogen in ex vivo fungal infected-rabbit cornea model. TPM with moxifloxacin revealed both the infecting fungal cells and corneal cells with 10-fold enhanced fluorescence. TPM with moxifloxacin may be useful for the detection of fungal keratitis because of the increased imaging speed.